A, The Pemberian Ultrasound dan Streching Pada Pelari Rekreasional dengan Plantar Faciitis Di Klinik Utama Motiva - Ardiani, Agis; Amallia, Firdausiyah; Alpiah, Dini Nur (ABDIKARYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
ABSTRACT Background: In Indonesia itself there is no clear prevalence of Plantar Faciitis cases, but one hospital in Jakarta stated that the frequency of patients with complaints of heel pain and Plantar Faciitis was 55.4%, and 22% in the runner population. Motiva is one of the sports health clinics in Jakarta where almost all of the patients are runners with sports-related injuries and plantar faciitis is the second most common after ankle cases. Treatment for Plantar Faciitis consists of physical therapy such as Massage, Mobilization, Ultrasound, Tens, and Taping as well as Stretching. It also has healing success and is often used in Plantar Faciitis programs. Objective: Find out more about the purpose of providing ultrasound and stretching to runners with plantar fasciitis at the Motiva Main Clinic. Method: This research uses a case study where the sample consists of 3 samples of patients who are included in the category of Runners with Plantar Faciitis with intervention 2-3 times per week for 8 meetings. Conclusion: Providing Ultrasound and Active Stretching can reduce pain and improve function in runners diagnosed with Plantar Faciitis, Keywords: Runners, Plantar Faciitis, Ultrasound, Streching.